The Impact of Total Quality Management on the Saudi Manufacturing SMEs Performance - Alghamdi, Rana Mansour Ali; Manickiam, Neelamehan A/L; Jantan, Amer Hamzah; Ibrahim, Saadiatul Binti (Advances in Social Sciences Research Journal, 2022)
The Saudi SMEs manufacturing sector suffered a low performance. This study aimed to investigate the impact of total quality management on Saudi SMEs' manufacturing performance and identify which practice of total quality management has the highest impact on Saudi SMEs' manufacturing performance. This study relied mainly on the total quality management indicators suggested by Crosby's model. The data for this study was collected based on a cross-sectional time horizon of 327 staff members belonging to the managerial levels. The findings of this study revealed that both training and employee involvement governance doesn't influence Saudi manufacturing SMEs. However, the rest of the total quality management dimension, namely continuous quality improvement, management leadership, and organizational innovation, have a significant and positive impact on Saudi manufacturing SMEs’ performance. It is strongly advised that the TQM model produced via the current study—which consists of TQM characteristics and benefits—be validated across all business sectors.